Increasing Family Economic Resilience During The Covid-19 Pandemic (Case Study of the Sidorejo Village Community, Tirto District, Pekalongan Regency) - Rizky Amalia; M. Aris Safii (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Family economic resilience is closely related to the ability to manage the family economy which includes clothing,food, and housing so that it can be fulfilled even though it is minimalistic. The current shock of the Covid-19pandemic has greatly impacted the distribution of household income and expenditure. Therefore, the purpose of thisstudy is to find out what efforts can be made to increase family economic resilience during the pandemic. Thisresearch is a type of research that uses a literature study method and uses a qualitative approach. The results ofthis study indicate that there are four steps that can be taken as an effort to increase family economic resilienceduring the pandemic, namely by creating additional sources of income with an online shop business, optimizingfamily assets by optimizing the home yard, being able to manage family finances during the pandemic withfinancial planning and implementing a simple lifestyle by doing habits according to needs and abilities.